Pendidikan Multikulturalisme - Fachrul Ghazi; Wahdatunnisa Wahdatunnisa; Ahmad Muthohar; Ida Farida; Siti Hadijah (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2012)
The slogan of Indonesia, Bhineka Tunggal Ika, should involve the concept and the implementation of diversity and mutlicultualisme to strengthen the unity of Indonesia people. In fact, there are still found many conflicts in Indonesia caused by the different religiouns and culture among Indonesian people and it will cause the obstacle to reach the unity in Indonesia. The different religioun and culture has not given any positif impact to Indonesia. Unfortunely, it causes some conflicts, misunderstandings, and fightings in Indonesia. To minimize it, the schools should teach the value of togetherness and tolerancy in adjusting and implementing the diversity. This kind of education can be taught by using the concept of multiculturalism education. As the representation of Indonesian diversity, it is an appropriate decision to have Kalimantan Timus as the subject of this multiculturalism research.